2018
DOI: 10.2196/jmir.9014
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Health Care Information Technologies: Evaluation of Trust, Security Beliefs, and Privacy as Determinants of Health Care Outcomes

Abstract: BackgroundThe diffusion of health information technologies (HITs) within the health care sector continues to grow. However, there is no theory explaining how success of HITs influences patient care outcomes. With the increase in data breaches, HITs’ success now hinges on the effectiveness of data protection solutions. Still, empirical research has only addressed privacy concerns, with little regard for other factors of information assurance.ObjectiveThe objective of this study was to study the effectiveness of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(29 citation statements)
references
References 50 publications
0
27
0
2
Order By: Relevance
“…A recent Eurobarometer survey requested by the European Commission showed that a majority of respondents would like Web-based access to their medical records, whereas the question whether they would like to grant access to their records to third parties depends on the type of recipient [9]. Moreover, earlier studies revealed that patient- (or more generally, user-) determined privacy controls and restrictions on the content and/or recipient may be a prerequisite of sharing [10,11], whereas privacy concerns and a lack of selective controls have a negative influence on the intention to share medical information even with other health care providers [12] and may reduce patient care quality [13]. As discussed in Caine et al’s study [14], patients would like to have granular privacy controls over their health information in medical records allowing them to differentially share their data in medical records or only parts of it, depending on the data recipient of and/or type of medical data.…”
Section: Introductionmentioning
confidence: 99%
“…A recent Eurobarometer survey requested by the European Commission showed that a majority of respondents would like Web-based access to their medical records, whereas the question whether they would like to grant access to their records to third parties depends on the type of recipient [9]. Moreover, earlier studies revealed that patient- (or more generally, user-) determined privacy controls and restrictions on the content and/or recipient may be a prerequisite of sharing [10,11], whereas privacy concerns and a lack of selective controls have a negative influence on the intention to share medical information even with other health care providers [12] and may reduce patient care quality [13]. As discussed in Caine et al’s study [14], patients would like to have granular privacy controls over their health information in medical records allowing them to differentially share their data in medical records or only parts of it, depending on the data recipient of and/or type of medical data.…”
Section: Introductionmentioning
confidence: 99%
“…Our survey does not presume anonymity, given this condition cannot be guaranteed for the provision of care, quality improvement, and some applications in public and private research. It further broadens the perspective for the general public, going beyond other studies that address populations receiving care or identified in ambulatory clinic settings [4849].…”
Section: Discussionmentioning
confidence: 99%
“…These issues have been raised not only in Korea but also in other countries. Kisekka and Giboney [ 16 ] found that privacy concerns reduce the frequency of patient access to health records use and positive attitudes towards the HIE. However, belief in the effectiveness of information security increases the frequency of patient access to health records and helps to develop a positive attitude towards the HIE.…”
Section: Discussionmentioning
confidence: 99%